Parasitism of a leafminer pest in managed and natural habitats - Salvo, Silvia Adriana (2005)
Parasitic assemblages of Liriomyza huidobrensis were analysed in relation to natural, urban and cultivated habitats through experimental and comparative methodologies. The ﬁeld experiment consisted in placing potted plants previously mined in the laboratory in four localities representative of each habitat type for seven days, whereas naturally mined Arctium minus leaves were collected over several years in localities representative of different environments. Results showed that overall parasitism and parasitoid species richness were not lower in simple and disturbed than in complex habitats. Pooled data indicated that parasitism of L. huidobrensis increased in the sequence natural < urban < culti- cultivated on both experimentally exposed and naturally occurring weeds. Small leafminer populations attracted the highest total number of parasitoid species in cultivated habitats. Some degree of habitat specialisation was detected in eulophid species which were particularly scarce in cultivated habitats, the reverse being found for braconids.